Evaluating a Tri-Institutional Cancer Research Capacity-Building Program for Early-Stage Investigators - Kathryn S. Maxwell; Lecarde Webb; Desiree Rivers; Ann Smith; Emily Hudson; Beverly Taylor; Shailesh Singh; Honghe Wang; Brian M. Rivers; Timothy Turner; Vivian L. Carter; Windy Dean-Colomb; et al. (Journal of Cancer Education, 2026)
The Comprehensive Partnerships to Advance Cancer Health Equity (CPACHE) initiative of the National Cancer Institute (NCI) supports long-standing collaborations between an under-resourced institution and NCI-designated Cancer Centers to strengthen cancer research workforce and advance cancer research capacity. One of the longest continuously funded CPACHE programs is the Morehouse School of Medicine/Tuskegee University/University of Alabama at Birmingham O’Neal Comprehensive Cancer Center tri-institutional partnership. A central component of this partnership is training future generations of investigators, which is accomplished through the research education programs that are designed to build cancer research skills, enhance mentorship, and support career development for all levels from high school students to Early-Stage Investigators (ESIs). This paper evaluates the longitudinal impact of a year-long program for ESIs and postdoctoral fellows since its inception in 2007. The data were extracted from the Research Education Core administrative records about the scholars and mentors and utilized publicly accessible databases Scopus and PubMed for publications, and the NIH RePORTER for grants. Among 89 program scholars, nearly 95% had at least one publication since their program start date. Of these, 70% had a first author, and 62% had a senior author publication. Approximately 20% of scholars obtained NIH funding as principal investigators through grants, core leadership, and/or supplements. This tri-institutional program successfully attracted investigators committed to cancer research. The outcomes suggest that structured training, intensive mentorship, and cross-institutional collaboration can meaningfully support their academic careers. These findings provide insights for strengthening similar programs to continue to meet the evolving professional needs for the development of ESIs and postdoctoral fellows, particularly at under-resourced institutions.